(untitled) (Clinics, 2019)
OBJECTIVE: To evaluate the impact of a complex-care-based medical school in the context of the Brazilian health care system on students’ career choices. METHODS: This was a retrospective cross-sectional study based on medical regulatory organization records. It included records for 7,419 physicians who graduated from FMUSP. Geographic data were analyzed using Kernel maps, and the statistical analysis was performed with SPSSs version 24.0. A p-value less than 0.05 was considered significant. RESULTS: Of the 7,419 physicians, 68.6% (95% CI 67.5-69.7) were male, and 20.7% (95% CI 19.8%-21.7%) had no medical specialty, compared to 46.4% nationwide. Internal medicine and surgery-based specialties were more popular, accounting for 39.4% (95% CI 38.3%-40.5%) and 16.8% (95% CI 15.5%-17.6%) of our study group, compared to the Brazilian averages of 25.9% and 13.5%. Our graduates also had a higher probability of staying in Sa˜o Paulo City, especially when born outside the city. CONCLUSION: We believe that FMUSP remains an interesting model for studying the impact of a highly specialized center on the education and career choices of medical students.